Професійна майстерність майбутніх учителів фізичної культури - Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina; Візавер Вікторія; Vizáver Viktória; Viktoriia Vyzaver; Ларіна Тетяна; Larina Tetiana (Видавництво «Код», 2024)
Резюме. У статті розкрито сутність поняття «професійна майстерність», окреслити шляхи її формування у процесі професійної підготовки майбутніх учителів фізичної культури. Професійну майстерність учителя фізичної культури розглянуто як сукупність якостей особистості, яка володіє професійною компетентністю, інноваціями в системі освіти, здатна до креативності, саморозвитку й характеризується сформованими громадянськими, морально-етичними якостями.

Abstract. The article reveals the essence of the concept of "professional skill", outlines the ways of its formation in the process of professional training of future teachers of physical education. The professional skill of a physical education teacher is considered as a set of qualities of a person who possesses professional competence, innovations in the education system, is capable of creativity, self-development and is characterized by formed civic, moral and ethical qualities. The elements of mastery are professional competence, possession of modern learning technologies, practical skills, pedagogical abilities, the presence of civil, moral and ethical qualities formed in the teacher. The combination of these components contributes to the formation of a successful modern teacher, competitive in the educational environment. The importance of the professional skill of physical culture teachers is expressed through such factors that are directly related to innovative technologies. The professional activity of future teachers of physical education and their professional skill should have health-preserving activities, ensure the influence on the physical and intellectual development of the personality of the students of education, have an innovative direction of the educational process on the formation of the physical potential of schoolchildren, the healthimproving development of personalities on the integral formation of well-rounded citizens of Ukraine with a clearly defined active position regarding national and cultural virtues. It is noted that the training of future specialists with the aim of forming their professional skills is expedient to be carried out in cooperation with the stakeholders of educational programs who have a legitimate interest in the educational activities of the institution of higher education and influence on the improvement of the quality of training of future specialists in order to ensure the positive dynamics of the growth of quality indicators of higher education. The most extensive in the multifaceted work of future teachers of physical culture is the formation of physical development of young people, which aims to strengthen health, develop physical, moral and intellectual abilities for the harmonious formation of their personality.
Professional skills of future physical education teachers
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015039 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-10
Keywords: професійна майстерність; здоров’язбережувальна діяльність; майбутні учителі фізичної культури; адаптація; професійна компетентність; інновації в системі освіти